Incentives and Employee Productivity in Private Organizations: A Case of Hannah Christian Aid - Bonita Rutabingwa (Uganda Christian University, 2024)
This research report was undertaken to investigate on incentives and employee productivity of Hannah Christian Aid. It was guided by three objectives; to find out the effect of recognition on employee productivity of Hannah Christian Aid, to analyze the effect of working conditions on employee productivity of Hannah Christian Aid, to assess the effect of career development opportunities on employee productivity of Hannah Christian Aid. The researcher used a sample size of 63 respondents then used questionnaires and interview guide to collect data which was later analyzed using the statistical package for social sciences. Results of the first objective shows that recognition has a significant effect on employee productivity of Hannah Christian Aid, Supported by the following responses; 54% of the respondents were positive to the statement that recognition increases employee morale, making them feel valued and appreciated, which leads to higher productivity; 62% were positive to the statement that recognition leads to higher employee engagement, as employees feel their work is meaningful and appreciated, which boosts productivity; 61% of the respondents were positive to the statement that employees who feel recognized are more satisfied with their jobs, which translates into higher productivity and better performance. Results of the second objective reveals that working conditions has a significant effect on employee productivity of Hannah Christian Aid and was supported by the following responses which include; 56% of the respondents were positive to the statement that good working conditions, like a comfortable workspace and adequate resources, help employees stay focused, leading to increased productivity, 80% of the respondents were positive to the statement that a well-organized and safe work environment enables employees to work more efficiently, reducing errors and boosting productivity while results of the third objective showed that career development opportunities provide employees with new skills and knowledge, which can directly improve their productivity supported by 75% were positive to the statement that offering career growth opportunities fosters loyalty, reducing turnover and ensuring a more experienced and productive workforce. There is need for the organization to create a culture of appreciation where achievements are regularly acknowledged. This can be done through both formal and informal recognition programs, such as employee of the month awards, public shout-outs during meetings, and personalized thank-you notes.